Analisis Regresi Data Panel Profitabilitas Bank Pembangunan Daerah (BPD) di Indonesia - Ghozi, Saiful; Hermansyah, Hadi (Jurnal Matematika; Vol 8 No 1 (2018), 2018)
The data obtained in banking and financial research is often in the form of panel data, while panel data is a combination of cross section and time series data. The aim of this paper is to apply panel data regression analysis to obtain an appropriate model. The case taken is the analysis of the influence of the ratio of Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) to the Return On Assets (ROA) of Bank for Regional Development (BPD) in Indonesia in the period 2012 to 2016. From the model specification test results obtained that the fit model is the Fixed Effect Model (FEM). The empirical test result between individual and time effect showed that fit model is is individual effect model, i.e.   slope coefficients constant but the intercept varies across 20 bank of BPD samples. The main LDR and NPL variables have no significant effect on ROA. While individual Bank BPD which has significant effect on ROA is BPD of DIY, BPD of Central Sulawesi, BPD of Southeast Sulawesi BPD of West Java BPD, BPD of East Java, and BPD of South Kalimantan.